An ultrasonic method for the investigation of coronary graft patency - NOWICKI, Andrzej; REID, John (Archives of Acoustics, 1983)
A new method and system for the visualization of blood flow in coronary grafts is presented. This method is based on the technique of stationary echo cancellation (SEC), phase detection and integration of Doppler signals in real time, using broad-band analog CCD delay lines. Preliminary results of examinations of coronary graft patency for 15 patients are presented.